HERMENEUTIKA FILSAFAT DAKWAH - Agus Fatuh Widoyo (Institut Islam Mamba'ul 'Ulum Surakarta, 2022)
Da’wah is a commandment of Allah swt to Muslims. Da'wah must be understood not only to convey, but more broadly, such as da'wah as an action whose essence through action is expected to bring change, especially in social life. Da'wah as a science needs to be developed and researched continuously to produce formulas for da'wah methods that are in accordance with the times, but still based on ethics that are in accordance with the times, but still based on ethics and standard syara' provisions. Empirically, da'wah science can be classified as a social science (social science) according to some experts. Therefore, hermeutics can be the basis and basis of epistemology in the development of the da'wah sciences.